Mathematical modeling and mechanisms of HIV latency for personalized anti latency therapies - Gianmarco Rasi; Elena Emili; Jessica M. Conway; Nicola Cotugno; Paolo Palma (npj Systems Biology and Applications)
Abstract Combination antiretroviral therapy controls human immunodeficiency virus-1 (HIV) but cannot eradicate latent proviruses in immune cells, which reactivate upon treatment interruption. Anti-latency therapies like “shock-and-kill” are being developed but are yet to succeed due to the complexity of latency mechanisms. This review discusses recent advances in understanding HIV latency via mathematical modeling, covering key regulatory factors and models to predict latency reversal, highlighting gaps to guide future therapeutic approaches.